2014
DOI: 10.1590/0047-2085000000001
|View full text |Cite
|
Sign up to set email alerts
|

Atitudes em relação ao corpo e à alimentação de pacientes com anorexia e bulimia nervosa

Abstract: rESUMo objetivo: Avaliar como se relacionam as atitudes alimentares e corporais de pacientes com anorexia ou bulimia nervosa. Métodos: Pacientes adultas de um ambulatório especializado, com diagnóstico de anorexia (n = 48) ou bulimia nervosa (n = 58), responderam à Disordered Eating Attitude Scale (DEAS) para avaliação das atitudes alimentares e ao Body Attitude Questionnaire (BAQ) para atitudes corporais -ambos traduzidos e validados para mulheres jovens do Brasil. A correlação entre os escores da DEAS e do B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
1
0
3
Order By: Relevance
“…Therefore, the results obtained in terms of their body attitudes are not surprising. Although their average scores on the BAQ differ considerably from the scores observed in young women with anorexia or bulimia and are similar to those of healthy females (Probst et al, 2008;de Souza et al, 2014), 20% of the participants showed negative attitudes towards their weight and body and feelings of contempt and lack of personal worth due to appearance, which is consistent with the prevalence observed in the present study for body dissatisfaction as well as with the percentage of players with the worst body perceptions and the greatest discrepancy between their perceived and ideal bodies. Women with disordered eating show significantly higher scores on the BAQ and its dimensions and this self-report-particularly the subdimensions of attractiveness, strength/fitness and selfdisparagement-allows discriminating between women with EDs and healthy females (Probst et al, 2008).…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, the results obtained in terms of their body attitudes are not surprising. Although their average scores on the BAQ differ considerably from the scores observed in young women with anorexia or bulimia and are similar to those of healthy females (Probst et al, 2008;de Souza et al, 2014), 20% of the participants showed negative attitudes towards their weight and body and feelings of contempt and lack of personal worth due to appearance, which is consistent with the prevalence observed in the present study for body dissatisfaction as well as with the percentage of players with the worst body perceptions and the greatest discrepancy between their perceived and ideal bodies. Women with disordered eating show significantly higher scores on the BAQ and its dimensions and this self-report-particularly the subdimensions of attractiveness, strength/fitness and selfdisparagement-allows discriminating between women with EDs and healthy females (Probst et al, 2008).…”
Section: Discussionmentioning
confidence: 75%
“…Como relata Souza et al, (2014), o profissional deve abordar as atitudes alimentares e corporais para ajudar a prevenir a recaída e a cronicidade do transtorno da compulsão alimentar periódica, pois com a descoberta de que o TA tem uma pior relação com a alimentação sugere que mais do que apenas os sintomas clássicos da compulsão alimentar periódica e da síndrome purgativa precisam ser abordados no tratamento. Acredita-se que quanto mais preocupados com a alimentação, os tipos de alimentos e a imagem corporal, mais fácil será para os pacientes apresentar compulsões e mais métodos compensatórios inadequados.…”
Section: Resultsunclassified
“…As experiências de vida envolvem a afetividade com os alimentos e na iminência de uma doença ameaçadora de vida não diminuem, incluindo recordações agradáveis que a comida desperta e o paciente oncológico experimenta são as sensações devido à ausência ou dificuldade de ingestão (Amorin, 2021). Tais pensamentos e sentimentos podem ser identificados por meio das atitudes alimentares, que consistem em crenças, pensamentos, sentimentos e comportamentos em relação à comida, e sofrem influências subjetivas, sociais, ambientais e culturais (Alvarenga, Scagliusi, & Philippi, 2010) As atitudes alimentares englobam a relação com alimento e, portanto, o comer ou não comer, em resposta a sensações e emoções Pisciolaro, Polacow, Cordás, & Alvarenga, 2014). Além disso, para manter um bom estado nutricional, é fundamental estabelecer e manter atitudes alimentares positivas, confiantes, confortáveis e flexíveis (Satter, 2007) Diante dos apontamentos elencados, questionou-se quais seriam as estratégias de enfrentamento utilizadas pelos pacientes oncológicos hospitalizados com doença progressiva, avançada e incurável, frente ao cuidado multiprofissional?…”
Section: Introductionunclassified